2009
DOI: 10.1007/s10103-009-0709-9
|View full text |Cite
|
Sign up to set email alerts
|

Topical imiquimod in conjunction with Nd:YAG laser for tattoo removal

Abstract: imiquimod plus laser therapy demonstrated a more favorable outcome when evaluated by the investigators or subjects. The mean scores for tattoo clearance from baseline to 2 months after completion of treatment with 5% imiquimod cream versus placebo cream were 4.3 versus 2.7 as rated by investigators and 4.7 versus 2.3 as rated by subjects. No textural changes were observed after therapy and were not shown to be different between the two groups. Further large-scale studies are important in developing a role for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 3 publications
0
11
0
1
Order By: Relevance
“…Treatment using a QS laser and imiquimod has been shown to clear tattoos more effectively than QS laser treatment alone in an animal model . To our knowledge, there have been only two human studies evaluating the use of imiquimod in conjunction with laser treatment of tattoos . These limited data are conflicting, and further human studies are needed.…”
Section: Types Of Tattoosmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment using a QS laser and imiquimod has been shown to clear tattoos more effectively than QS laser treatment alone in an animal model . To our knowledge, there have been only two human studies evaluating the use of imiquimod in conjunction with laser treatment of tattoos . These limited data are conflicting, and further human studies are needed.…”
Section: Types Of Tattoosmentioning
confidence: 99%
“…70 To our knowledge, there have been only two human studies evaluating the use of imiquimod in conjunction with laser treatment of tattoos. 71,72 These limited data are conflicting, and further human studies are needed.…”
Section: Laser Treatmentmentioning
confidence: 99%
“…Dermabrasion (to remove the epidermis) has also been used for tattoo removal, with tattoo pigment mobilized and extruded from the inflamed skin into a dressing covering the treatment site 28,29. Increased tattoo pigment phagocytosis has also been proposed as a mechanism for imiquimod and dermabrasion 29,30. However, ingenol mebutate activates PKC,18 which is reported to suppress phagocytic activity of neutrophils 31,32.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies have shown inconsistent results, with a study in 3 patients suggesting that imiquimod facilitated tattoo removal in conjunction with laser treatment,30 whereas another study in 19 patients reported that imiquimod was ineffective in this setting 36. Whether ingenol mebutate could synergize with laser treatment to facilitate tattoo removal in humans without cicatrix formation clearly remains to be tested, given that there are substantial differences between mouse and human skin 37…”
Section: Discussionmentioning
confidence: 99%
“…La combinación del uso de imiquimod con el tratamiento con láser puede provocar una mejor eliminación del pigmento de tatuaje en cobayas (22). La combinación del láser Q-switched de alejandrita e imiquimod crema en el grupo tratado mostró que clínica e histológicamente tienen menos pigmento que los tatuajes que fueron tratados únicamente con láser, aunque algunos autores describen experiencias diferentes en su práctica (23,24).…”
Section: Imiquimodunclassified